Customary Law System Againts The Distribution Of Inheritance In South Aceh Regency - Asy'ari Asy'ari; Muhammad Faisal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
South Aceh is an area with a variety of tribes and cultures that have a uniqueness compared to other regions in Aceh. In terms of the division of heritage of the people of South Aceh has its own traditions that have been done for generations since long ago. This research aims to find out how the practice and philosophy of heritage distribution in the people of South Aceh Regency. The research method used is field research with qualitative patterns. In the discussion use descriptive methods of analysis. The results of the research obtained, namely thedistribution of heritage in South Aceh Regency can be seen from several aspects, namely First;the people ofSouth Aceh majority divide inheritance based on customary law, but there is also a small percentage who divide inheritance using Islamic law. Inheritanceis only divided for children who died. Second; The time of division of inheritance in South Aceh society varies, some are divided when the parents are still alive, when one of the parents dies, when both parents die and there is also a split after a very long time. Third; The number of parts of inheritance divided varies, some divide the male share larger than the female, the female part is greater than the male and there is also a large divide between men and women. Fourth; There are others outside the heirs who get a share of the inheritance such as adopted children, nieces and caregivers of parents.